A rare cause of recurrent haemolytic anaemia: carboplatin and paclitaxel-induced autoimmune haemolytic anaemia - Yingchoncharoen, Pitchaporn; Thongpiya, Jerapas; Maharjan, Shrinkhala; Abdelnabi , Mahmoud; Kim, Samuel; Saowapa, Sakditad; Lalmuanpuii, Judy (European Journal of Case Reports in Internal Medicine, 2023)
Drug-induced immune haemolytic anaemia (DIIHA) is a rare but serious complication affecting approximately 1 in 1,000,000 patients, but its incidence might be underestimated due to misdiagnosis. Several factors should be considered to ensure an accurate diagnosis, including previous medical history, comorbidities, drug history, the temporal relationship between drug exposure and symptom onset, haemolytic features, and comorbidities in suspected cases. The authors report a case of DIIHA caused by combination chemotherapy with carboplatin and paclitaxel complicated with haeme pigment- induced acute kidney injury.